2020
DOI: 10.21203/rs.3.rs-83268/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitudes and practices about Coronavirus disease (COVID-19) among Birzeit University students: A cross-sectional study

Abstract: Aim: COVID-19 the novel corona virus that has been characterized as a pandemic; as it spreads all over the world and has so far infected more than 20 million worldwide. In Palestine, the first seven cases were documented on March 5th, 2020 followed by the declaration of the state of emergency. This study aimed to assess knowledge, attitudes and practices toward COVID-19 among Birzeit University students.Subject and methods: A cross sectional study was carried out, a questionnaire was developed based on the WHO… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
3
4
2
Order By: Relevance
“…The study also showed that more than half (58.2%) of the students knew the correct incubation period of the disease. This finding is much lower than study from Palestine (95.8%) 16 and lowers than study from China (66.4%). 11 The possible suggestions for such variations may be due to variations of sample characteristics, in which the numbers of students from health sciences related field involved in the study from Palestine and China are more than this study.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The study also showed that more than half (58.2%) of the students knew the correct incubation period of the disease. This finding is much lower than study from Palestine (95.8%) 16 and lowers than study from China (66.4%). 11 The possible suggestions for such variations may be due to variations of sample characteristics, in which the numbers of students from health sciences related field involved in the study from Palestine and China are more than this study.…”
Section: Discussioncontrasting
confidence: 73%
“…The study showed that (47.0%) of the students had good knowledge about the Covid-19. This finding is better than studies done in Beret (41.4%) 16 and India (40%). 12 This difference could be due to difference in methods of categorizations to good and poor knowledge, in which the late Indian study used arbitrary cutoff 70% and that of the current study used the mean knowledge score as the cutoff value to dichotomize poor and good knowledge.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Similar results were reported in Palestinian, Ugandan, and Iranian studies. 2 , 21 , 22 Concerning the treatment and preventive measures, wearing masks and social isolation for 14 days for someone exposed to COVID‐19 were sustained as preventive strategies by respondents. This is in agreement with reports from studies in China for wearing masks 23 and in Jordan and Saudi Arabia for social isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies conducted in Palestine, the first one was performed among students at Birzeit University showed that students had varying degrees of knowledge about COVID-19, and most of them relied on the official media briefs as a source of information. The majority of them carried out positive and cautious practices regarding the COVID-19 epidemic [3]. While the other study done at two colleges of nursing of Arab American and Al-Quds University revealed that students had an adequate level of knowledge about COVID-19 and negatively attitude toward it [1].…”
Section: Introductionmentioning
confidence: 96%